Caminos cruzados filosofía y literatura del exilio español en América Latina - Chihaia, Matei; Ferrer Ortega, Jesus Guillermo; Pérez-Gatica, Sergio; Schmich, Niklas (Ediciones de Iberoamericana, 2023)
Studying the dialogue between literature and philosophy in the Spanish exile in Latin America requires a historiographical effort, since the exile is framed in a historical before and after: in the "before" of its traditional context, that of the ideas belonging to the place of origin prior to exile. These ideas, capable of developing or changing in the "after" of the post-exile world (in this case, the Spanish-American world), give life to the poetic and philosophical works gestated in the land where the exiles found the protection and shelter of a new homeland: Argentina, Colombia, Cuba, Mexico, Venezuela. This book offers interdisciplinary elements to map the paths in which a group of authors whose life and work was marked, directly or indirectly, by the experience of exile cross: Max Aub, Luis Cernuda, José Gaos, Manuel García Morente, Juan Larrea , Eduardo Nicol, Alfonso Reyes, Josep Solanes and María Zambrano. The texts thematize the work, context, and influences of writers, poets, and philosophers who arrived in Latin America fleeing political persecution and the Civil War in Spain. Many of the exiles saw in the nation that welcomed them the opportunity for a new beginning, others, on the other hand, the place of eternal nostalgia and permanent mourning for their lost home. In all cases, this circumstance was reflected in the work of the exile authors discussed here, in their efforts to reinvent literature, philosophy or the relationship between the two, as well as in their contributions to the dissemination of these two disciplines in organs cultural institutions such as educational institutions, publishing houses and magazines.